La didáctica de la literatura inglesa con textos poéticos - Asunción Barreras Gómez (Universidad de La Rioja, 2013)
A student's first contact with English literature should be done taking into account the age, attitude, level of English and motivation of the learner. The selected text should provide a balance between the reader and the text thus assuring that the text will not be rejected. The texts should be coherent and progressively difficult. They should also use topics which are appropriate to the student. Primary Education English pupils possess different characteristics from those of university students. The teacher must also use graded literary texts so as to make both pupils and students respond in the desired manner. This is supposing that the teacher has a wide knowledge of literature and psychology and is thus able to choose the appropiate texts. Teachers use English literature for a variety of reasons these being improving linguistic competence, getting the students used to reading in English orto teach more about the country in question. There are also teachers who choose literary texts that their pupils will understand, the reason being that there are many books whose cultural references or language are too difficult for the pupils. The teachers take all these features into account in order to be able to provide the optimum learning conditions for the pupils. In providing these conditions the pupils are also helped to develop their literary competence so that they will appreciate the different styles, forms, conventions or symbols that can be found in the texts.